2011
DOI: 10.2147/dmso.s27050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of demographic and clinical characteristics influencing health-related quality of life in patients with diabetic foot ulcers and those without foot ulcers

Abstract: BackgroundA number of studies have demonstrated that health-related quality of life (HRQoL) is negatively affected by diabetic foot ulcers. The aim of this study was to compare HRQoL in diabetic patients with and without foot ulcers and to determine demographic and clinical factors influencing HRQoL.MethodsThere were no variables affecting HRQoL except for gender in diabetic patients without foot ulcers. Demographic and clinical variables were recorded and HRQoL was evaluated using the Short Form 36 (SF-36) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 22 publications
5
43
4
3
Order By: Relevance
“…The patients in the age group of 51-60 years were most significantly infected with diabetic foot infections. The findings of this study are similar to the one reported by Yekta et al [23] in which patients in the age group of above 50 years compared to less than 50 years and the mean age of the patients were 60.73 ± 11.3 years. The main reason attributed to this is mainly due to their physical conditions along with the associated other factors of the patients in this age group.…”
Section: Discussionsupporting
confidence: 92%
“…The patients in the age group of 51-60 years were most significantly infected with diabetic foot infections. The findings of this study are similar to the one reported by Yekta et al [23] in which patients in the age group of above 50 years compared to less than 50 years and the mean age of the patients were 60.73 ± 11.3 years. The main reason attributed to this is mainly due to their physical conditions along with the associated other factors of the patients in this age group.…”
Section: Discussionsupporting
confidence: 92%
“…28,29 To promote QoL among thalassemic patients, a variety of factors should be taken into account by health-related policymakers, with special attention to patients presenting any comorbid diseases, poor compliance with iron-chelating therapy and lower socioeconomic status. Psychosocial support should be scheduled for patients and their families in order to prevent mental health issues, behavioral problems and illness complications.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Saudi Arabia suggested different mechanisms of elevated cardiovascular risk between men and women: in women, elevated IL‐6 and C‐reactive protein predicted insulin resistance and hypertension, respectively, while these relationships did not hold for men . Health‐related quality of life was lower in female vs. male type 2 diabetes patients in Iran .…”
Section: Methodsmentioning
confidence: 99%